ANALISIS KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS V SDN DARANGDAN TINGKAT - Daniar Rosdiana; Rosita, Neneng Tita; Yuliawati, Lia (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
This study aims to analyze the numeracy literacy skills of fifth grade students of SDN Darangdan Tingkat in using numbers and mathematical symbols, analyzing information, and interpreting the results of the analysis for decision making. The method used is descriptive analysis by collecting data from students' answers to various questions that test numeracy literacy skills. The results showed that overall, students' numeracy literacy skills reached 46.78%, which is included in the “Fair” category. In the first indicator, learners reached 58.88% in using numbers and mathematical symbols. However, in the second indicator, relating to information analysis, the percentage of achievement was only 27.03%, indicating significant difficulties in analyzing data. The third indicator, interpreting the results of the analysis, showed an achievement of 54.44%. These findings indicate the need for more attention in improving learners' data analysis skills through more interactive and contextualized learning methods.